2016
DOI: 10.1097/md.0000000000005098
|View full text |Cite
|
Sign up to set email alerts
|

Long-term complications of splenectomy in adult immune thrombocytopenia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 31 publications
4
67
1
3
Order By: Relevance
“…Moreover, ITP could be associated with increased risk of thromboembolism 32,33 as well as splenectomy, performed in four of the nine patients exhibiting venous thrombosis, because of lack of sustained response with rituximab. 34,35 Several studies suggested that ITP could be associated with increased risk of hematologic malignancies. [36][37][38] In our study, we found no over-representation of late-onset malignancy, and the SIR was similar to the general French population, which gives reassuring data for the use of rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ITP could be associated with increased risk of thromboembolism 32,33 as well as splenectomy, performed in four of the nine patients exhibiting venous thrombosis, because of lack of sustained response with rituximab. 34,35 Several studies suggested that ITP could be associated with increased risk of hematologic malignancies. [36][37][38] In our study, we found no over-representation of late-onset malignancy, and the SIR was similar to the general French population, which gives reassuring data for the use of rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…We included populationbased/administrative cohort studies (N=5), retrospective (N=7) and prospective (N=2) cohort studies that reported outcomes on at least 50 patients with ITP, with a median follow up greater than 3 months. 22,55,[68][69][70][71][72] For the splenectomy patients in particular, we included only studies that reported late (>3 months) venous thromboembolism events to minimize selection bias from studies focusing on postoperative portal and splenic vein thrombosis. Time is calculated from date of splenectomy in the splenectomy group and date of enrollment in cohort for the nonFor personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…65 In patients with ITP, splenectomy usually increases the platelet count, and may also result in increases in plasma cholesterol, leucocyte counts, and C reactive protein, all of which are associated with increased thrombotic risk. 71 which may be due to the prospective design with closer follow-up. However, the cohort was small and significant attrition resulted in few patients followed beyond 20 years.…”
mentioning
confidence: 99%
“…Kaplan-Meier estimates of (A) progression-free survival and (B) overall survival based on International Myeloma Working Group uniform response criteria per site review. Autologous 111 Indium-oxinate-labelled platelet sequestration study in patients with immune thrombocytopenia treated by thrombopoietin receptor-agonists An increasing number of patients treated with thrombopoietin receptor-agonists (TPO-Ras) for immune thrombocytopenia (ITP) are reluctant to undergo splenectomy mostly because of the irreversibility of the procedure and concerns about its long-term safety (Kojouri et al, 2004;Boyle et al, 2013;Thai et al, 2016). Isotopic assessment of the site of platelet destruction using autologous 111 Indium-oxinatelabelled platelet kinetic study might help to determine whether or not splenectomy is indicated in these patients (Najean et al, 1997;Sarpatwari et al, 2010;Palandri et al, 2014).…”
Section: Supporting Informationmentioning
confidence: 99%